Properties of heat-treated rubberwood using Direct Contact Method - Chia, Zi Bin (2018)
Wood source especially those high quality species is become lesser and the pressure of wood supply to community become higher. This is because the demand of market is higher. This study is describes the effect of thermal modification by using Direct Contact Method on physical and mechanical properties on rubberwood with different thickness, temperature and time of treatment. The samples of rubberwood were prepared in 1cm, 1.5 cm and 2cm thickness and treated at 160°C, 190°C and 220°C with 15 minutes, 30 minutes, 45 minutes and 60 minutes. The testing were done to treated samples. Physical properties were determined by water absorption and volumetric change while mechanical properties were determined by modulus of rupture and modulus of elasticity. The result showed that thickness of samples was significantly affect both physical and mechanical properties. However, temperature of treatment was not significantly affect to both physical and mechanical properties. Time of treatment was only significantly affect the volumetric change at 24 hours and modulus of elasticity.